Rice Paddles and Pink Helmets. Framing Gendered Resistance in 20th Century Japan - Barbara Molony (International Quarterly for Asian Studies, 2022)
Two Japanese women’s organisations – Shufuren, founded in 1948 and still in existence, and Chūpiren, founded in 1972 and disbanded in 1977 – appear to be vastly different from one another. And yet, they had one critical similarity: their use of accessories to make a political point. Shufuren members were advocates for consumer rights (and in the immediate postwar era, for food availability). Since then, they have demonstrated for such political issues as food safety, recycling, environmental protection and anti-nuclear energy, all in the name of their roles as wives and mothers. When demonstrating, they always appear bearing large mock-ups of the rice paddle used in Japan to scoop rice from the cooking pot. The rice paddle was a powerful symbol of women’s domestic and political strength. Chūpiren women, on the other hand, distinguished themselves in their advocacy of reproductive rights not only by their forcefulness but also by wearing pink helmets. Chūpiren saw value in street theatre and sensationalism. No other radical feminist group in the mid-1970s wore uniforms. The media at that time mocked Chūpiren’s helmets and attention-grabbing tactics, and in the process disparaged contemporary feminism as a whole.